2010
DOI: 10.1002/cmdc.200900467
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling Studies on the Human Neuropeptide S Receptor and Its Antagonists

Abstract: Neuropeptide S (NPS) is a 20-residue peptide of great interest due to its potential involvement in several biological processes such as arousal, anxiety, and food intake. The NPS receptor belongs to the rhodopsin-like G-protein-coupled receptor superfamily, and several polymorphisms and isoforms of this receptor are associated with asthma, allergies, and bronchial hyper-responsiveness, in particular the Asn 107 Ile mutation. Limited structural information is available for this peptide-receptor system, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Analysis of the model suggested that the residues isoleucine at position 107 (Ile107), cysteine at position 197 (Cys197), arginine at position 241 (Arg241), and glutamine at position 344 (Gln344) are localized on different sides of the transmembrane protein: Ile107 is at the extracellular end of the H2 helix, Cys197 is at the bottom of the second extracellular loop, Arg241 is positioned on a cytosolic domain that links helices H5 and H6, while Gln344 is localized on a short intra-cytosolic helical stretch at the end of the H8 helix (figure 5A). These results are in accordance with a recent study where the interactions of NSPR with several non-peptide antagonists were modelled, and where a similar localization for the residue107 on the terminal portion of the second transmembrane helix (H2) was reported [38]. Importantly, our model indicated that the side chain of Cys197 forms a disulfide bridge with the side chain of residue cysteine at position 121 (Cys121) within the core of the NPS binding domain (figure 5B).…”
Section: Resultssupporting
confidence: 93%
“…Analysis of the model suggested that the residues isoleucine at position 107 (Ile107), cysteine at position 197 (Cys197), arginine at position 241 (Arg241), and glutamine at position 344 (Gln344) are localized on different sides of the transmembrane protein: Ile107 is at the extracellular end of the H2 helix, Cys197 is at the bottom of the second extracellular loop, Arg241 is positioned on a cytosolic domain that links helices H5 and H6, while Gln344 is localized on a short intra-cytosolic helical stretch at the end of the H8 helix (figure 5A). These results are in accordance with a recent study where the interactions of NSPR with several non-peptide antagonists were modelled, and where a similar localization for the residue107 on the terminal portion of the second transmembrane helix (H2) was reported [38]. Importantly, our model indicated that the side chain of Cys197 forms a disulfide bridge with the side chain of residue cysteine at position 121 (Cys121) within the core of the NPS binding domain (figure 5B).…”
Section: Resultssupporting
confidence: 93%
“…This information can be extremely useful for the refinement of the recently proposed molecular models of NPSR and its binding pocket. 12 As already mentioned in the introduction, the relevance of ligand chirality for NPSR binding is also corroborated by the fact that the biological activity of chemically different molecules, such as the quinoline 13 and the tricyclic imidazole 14 compounds, could be attributed to a single bioactive enantiomer.…”
Section: Resultsmentioning
confidence: 78%
“…Molecular modelling studies investigated non-peptide ligand binding to NPSR. 12 In the frame of these studies, docking analyses were performed and a defined NPSR binding pocked was proposed; of note, only the (S) enantiomer of compound 1 was used in such simulations. The importance of ligand chirality for NPSR interaction has been recently supported by the identification of two novel classes of non-peptide NPSR antagonists: the quinoline 13 and the tricyclic imidazole 14 based compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis was performed with the aid of the CASTp tool available at the http://sts.bioengr.uic.edu/castp/ link [59] that we already employed for the calculation of the cavity volume of a 3D model of the Neuropeptide S Receptor [60]. The volume of the rP2X7 binding cavity was hence calculated and the same analysis was performed with the rP2X1 and rP2X3 structural models for comparison.…”
Section: Resultsmentioning
confidence: 99%